Khaldunian Understanding of Economico-Legal Philosophy: A Living Mechanism for Civilizational Existence - Mohammad Zakaria (İbn Haldun Çalışmaları Dergisi, 2020)
Ibn Khaldun is one of the erudite Islamic polymaths. Though he had contributed, as the biographic corpus suggests, to wide range of sociology, jurisprudence, historiography and economico-political philosophy, Ibn Khaldun is best known for his historiographical contribution. Hence his dynamic economic understanding, though pre-modern yet well capable of answering even the postmodern economic questions, almost remains terra incognita to many people. This paper, in adopting doctrinal method and comparative jurisprudential approach, has attempted to explore Khaldunian economic views with special focus on examining the core characteristics of three ideas of kasb maʻāsh and jibāyah (later referred to as KAMAJ) as to how these three tools, if developed and cultivated in a mutually exclusive framework, make a given nation blossom and flourish, and absence of which, especially rigging jibāyah (taxation) policy, may corrode production industries, consequentially leading a given country to the cataclysmic escalation of decadence and disappearance from civilizational cartography. By so presenting, the study has demonstrated that Khaldunian economic conceptions would be a better alternative-not pioneer in the theorization of economics as seen by some academics-to the western economic thought.